PERANAN EYE CATHCER DALAM IKLAN DAN MASALAH PENCARIANNYA - Kristiana, Nova (Nirmana, 2007)
Eye Cathcer represents one of the determinant factors for succeeding in an advertisement. The main objective in advertising is to get positive response from the consumer, to use the product offered, through advertisements and to position the product image in the consumer’s mind. Advertisements that go to and fro have various styles from the products offered. Advertisers also must think deeper on how to attract consumers so that the products offered are appropriate towards the sales target. This article will discuss the attraction in the different kinds of ads and how to look for attraction in the ads. Abstract in Bahasa Indonesia: Eye cathcer merupakan salah satu faktor penentu berhasil tidaknya suatu iklan. Tujuan utama beriklan adalah memunculkan respons positif konsumen untuk memakai produk yang ditawarkan melalui iklan dan memposisikan image produk di benak konsumen. Iklan yang berlalu-lalang memiliki berbagai macam daya tarik dari produk yang ditawarkan. Pengiklan juga harus berpikir lebih dalam untuk menarik konsumen supaya produk yang ditawarkan sesuai dengan target penjualan. Tulisan ini akan membahas daya tarik apa saja yang ada dalam iklan dan bagaimana cara mencari daya tarik yang ada pada iklan tersebut. Kata kunci: eye cathcer, iklan, konsumen